Optimalisasi Kapasitas Kader Posyandu melalui Program Nutrition Hero dalam Pembuatan Pangan Lokal Bergizi sebagai Pemberian Makanan Tambahan Balita - Nita Anggi Purnama; Rikha Surtika Dewi; Fajar Nugraha; Irmayanti Irmayanti; Aliya Fadlila Sya’bana (Forum Kerjasama Pendidikan Tinggi, 2026)
Posyandu cadres play a strategic role in improving community health status, particularly through nutrition education and the implementation of supplementary feeding programs for toddlers. However, limited knowledge and skills among cadres in utilizing local food resources as ingredients for nutritious supplementary food remain a challenge in optimizing posyandu services. This community service program aimed to improve the capacity of Posyandu Sukamaju 2 cadres in Mulyasari Village, Tamansari District, Tasikmalaya City, through training on the production of nutritious local food as an effort to support toddler nutrition fulfillment and family food security. The program was implemented through four stages: socialization, training, mentoring and evaluation, and the development of program sustainability strategies. The training activities employed interactive lectures, discussions, and hands-on practices in preparing nutritious local food products. Evaluation was conducted using pre-test and post-test instruments to measure participants’ improvement in knowledge. The results showed that the program successfully improved cadres’ knowledge and skills across all measured indicators, with the average pre-test score increasing from 70.73% to 87.82% in the post-test. In addition, cadres successfully produced several local food-based supplementary feeding products, including pumpkin pudding, spinach dim sum, chicken tofu nuggets, and shrimp chicken meatballs. The program also enhanced cadres’ readiness as nutrition education agents in the community and encouraged the utilization of local food resources as nutritious, practical, and sustainable supplementary feeding alternatives. Therefore, the Nutrition Hero program has the potential to strengthen posyandu services while supporting efforts to prevent nutritional problems among toddlers and improve family food security. The success of this program demonstrates that strengthening cadre capacity through practice-based activities can enhance independence in providing nutritious food. The skills acquired by cadres support the implementation of local food-based supplementary feeding programs (PMT) and have the potential to be developed sustainably within the community.